Perfil sociolinguístico de surdos em municípios com baixa ocupação territorial no Estado do Tocantins - Santos, Fernando Cardoso dos (Universidade Federal de São Carlos, 2024)
Sociolinguistic research in deaf communities is a still scarce scientific field, especially with regard to investigating the use of Brazilian Sign Language (Libras) and the contact of this language with other languages, such as Portuguese. Studies in this field deal almost exclusively with issues of linguistic variation and change in oral majority languages and border languages, which are also oral. Considering the complexity of studies of deaf communities and people, this research had its pillars supported mainly by the theoretical current of Sociolinguistics, which addresses issues related to bilingualism, language contact, language policies, and, in particular, the studies by Lucas (2004), which opened horizons for sociolinguistic studies of sign languages, arguing that these languages have the same sociolinguistic particularities and importance in the construction of a people in their sociocultural scope, independently of other languages. Based on these notes, in this research, the sociolinguistic profiles of deaf people were investigated, with the aim of describing characteristics related to family life and society, in addition to issues related to education, in municipalities with little territorial occupation in the state of Tocantins, considering the interaction, contact between Libras and the Portuguese language, in a way that could or could not confirm whether it is possible to have communication and understanding between deaf-deaf and deaf-hearing individuals, although they do not have fluency in a systematized language such as Libras. The research has a qualitative and descriptive approach and includes survey, investigations and data analysis, so that it can answer the questions and hypotheses listed. In the field research, a pre-structured questionnaire was developed and applied in an interview format with 30 deaf participants living within a minimum radius of 70 and a maximum of 300 kilometers from the capital Palmas, in the state of Tocantins. Surveys were carried out followed by contact with participants to carry out the interview, in person with participants living close to the researcher and virtually, via WhatsApp, with participants living in distant locations. In contact with the deaf, their communicative particularities were considered, that is, the interview was carried out orally and signed with the deaf spoken, in Libras, with the deaf who knew Libras, in gestures, mimes and iconic signs, with those who communicate through this means. The results show that, despite multiple and diverse contexts, there are possibilities for communication and understanding between speakers involved in environments where multiple languages are spoken, whether they are covered by the linguistic system or not, such as gestures, mime, homemade signs. These results also reveal that there is an urgent need to review municipal and state linguistic planning, in a way that promotes access for deaf people to the language in which they feel comfortable and boosts their sociolinguistic and cognitive development in general. It is concluded that the sociolinguistic profile of deaf people is diverse and it is possible for communication/interaction to occur harmoniously, with understanding between the actors involved, as long as multiple and multimodal communication resources are considered, in addition to Libras and the Portuguese language.
Sociolinguistic profile of deaf people in municipalities with low territorial occupation in the State of Tocantins
Keywords: Perfil sociolinguísitico; Sociolinguistics profile; Comunidade surda; Deaf community; Libras; Tocantins; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::SOCIOLINGUISTICA E DIALETOLOGIA